Morbidity patterns among pre-school children of migrant mothers in Sri Lanka - G. A. T. K. Athauda; D. N. Fernando (College of Community Physicians of Sri Lanka, 2002)
Objectives: To assess the prevalence and morbidity pattern, health care seeking behaviour and the distribution of some factors associated with morbidity among three defined groups of preschool children from a low socio-economic background, in relation to the maternal employment status. Special emphasis was given to the children of mothers employed overseas.   Methodology: Three groups of children between ages 13 -59 months from three MOH areas in the Colombo district were selected for the study.   Group 1- children whose mothers were working overseas as a domestic helper for a period of more than 06 months.   Group 2- For each child in group 1, a child matched on age and sex, having a mother employed in Sri Lanka for more than six months, as identified from the same neighbourhood.   Group 3- Similarly, a child matched on age and sex, whose mother was not formally employed was identified from the same neighbourhood.   An interviewer administered questionnaire was used to collect information on socio-economic status of the children, health care utilization pattems and some factors associated with morbidity.   After the preliminary household survey, all the children were followed up for a period of six months by the Public Health Midwife (PHM) using an information sheet to record information, on episodes of illnesses the children experienced   Results: Some of the variables which were differently distributed in the three groups were educational level of the father, indulgence in alcohol and drugs among the fathers, marital disharmony in  the families, gardens with faecal pollution, number of visits to the Child Welfare Clinic. The highest mean number of illness episodes were seen in the group 1 (2.8) compared to groups 2 (2.0) and group 3 (2.4).   Conclusions: Women of low income groups seek employment overseas, to improve their economic standards. The pre-school children of these mothers seem to be an important group for which special child welfare activities should be aimed at.